Successful treatment of dupilumab in Kimura disease independent of IgE: A case report with literature review - Yang, Boyun; Yu, Hanxiao; Jia, Minyue; Yao, Wo; Diao, Ran; Li, Bohui; Wang, Yongfang; Li, Ting; Ge, Liuya; Wang, Huiying (Frontiers in Immunology, 2022)
Kimura disease (KD) is a rare and benign chronic inflammatory disease of unknown cause. It is characterized by subcutaneous granuloma of soft tissues in the head and neck region, increased eosinophil count, and elevated serum IgE. No definitive treatments are recommended currently. A 57-year-old Chinese man was diagnosed with KD after 7 years of slow subcutaneous masses growth. The patient underwent the treatment of oral glucocorticoids for 1 year, but the masses recurred as the dosage tapering down. Subsequent anti-IgE therapy of Omalizumab administered subcutaneously at 450mg/day at a four-week interval didn’t show improvement. The size of masses didn’t decrease significantly as well as serum IgE and circulating eosinophils after 19 cycles of continuous treatment. Ultimately, switched strategy of dupilumab was applied at an initial dose of 600 mg, following by 300 mg every 2 weeks for 4 months. This treatment demonstrated dramatical effects with reduced masses in each area and fast dropdown of eosinophil counts. While the high level of serum IgE remained without changes. Recently, different biologic including anti-IgE, anti- IL-5 and anti-IL-4/IL-13 have been applied to treat KD with satisfied results and also help to explore the pathogenesis of this rare disease. To our knowledge, this is the first report that demonstrates the effects of two different biologics in the same patient, and reveals the impressive clinical efficacy of dupilumab to treat KD independent of IgE. Therefore, it is valuable to the further investigation of the underlying mechanism and the development of diagnosis and treatment of KD.